Minimally Invasive Dentistry: Parent/Carer Perspectives on Atraumatic Restorative Treatments and Dental General Anaesthesia to the Management of Early Childhood Caries - Arrow, Peter; Forrest, Helen; Piggott, Susan (Frontiers in Oral Health, 2021)
Introduction —Parents of children treated under dental general anaesthesia (DGA) have reported feelings of concern and anxiety. This study elicited the views of parents/carers (P/C) of children with early childhood caries (ECC) who participated in a randomised trial which tested the effectiveness of care under DGA or care using alternative minimally invasive Atraumatic Restorative Treatment and the Hall Technique approaches (ART/HT). Methods — P/C of children treated using the ART/HT (test) approach or care under a DGA (control) were interviewed. Focus group semi-structured interviews with P/C were undertaken in community facilities. The transcripts were read and inductively coded into domains to identify emergent themes. The codes were entered into NVivo software to assist data management and were further refined into broad themes. Results — Seven grouped interviews with 14 participants were conducted and one test participant provided a written response. Five broad themes emerged after thematic analysis: 1. Impacts on the child and the family; 2. child-/family-centred care; 3. Timeliness of care; 4. Affordable care; 5. Accessible care. Impacts were related to that of the effects of the disease, and of the care for the disease. Child-centred/family-centred care (CCC) was a source of appreciation by P/C of both groups when it was experienced. Frustration at the lack of timely care of their child’s treatment needs, coupled with the perceived expensiveness of care and difficulties in physically getting to the location for a specialist consultation was expressed by P/Cs in the study. Discussion — The use of the ART/HT enabled the establishment of a relationship between the clinical team and the child and P/C which was central to the delivery of CCC. P/Cs in the DGA arm of the study expressed dissatisfaction more often with the issues of timely care, cost of care and accessibility of care. P/C of both groups were equally satisfied with the treatment, where treatment had been received in a timely, child-centred manner. Conclusion — The findings suggest that minimally invasive approaches which facilitated CCC are acceptable alternative options to the DGA and should be considered for the management of ECC.